Adipose‐Derived Stem Cells Combined With Inorganic Bovine Bone in Calvarial Bone Healing in Rats With Type 2 Diabetes. Issue 4 (1st April 2014) - Liang, Lihua; Song, Yingliang; Li, Long; Li, Dehua; Qin, Mingqun; Zhao, Jianhui; Xie, Chao; Sun, Daocai; Liu, Yan; Jiao, Tiejun; Liu, Naibin; Zou, Guike
Abstract : Background: Clinical studies have revealed that patients with type 2 diabetes mellitus (DM) have higher implant and bone grafting failure rates than the general population, likely owing to inferior bone healing. The authors sought to investigate whether adipose‐derived stem cells (ASCs) combined with inorganic bovine bone improves bone repair in calvarial vertical critical‐sized defects (CSDs) in rats with type 2 DM. Methods: Bovine bone alone or seeded with 3 × 10 5, 3 × 10 6, or 3 × 10 7 ASCs/graft was randomly transplanted into calvarial CSDs in rats with DM induced by a high‐fat diet with low‐dose streptozotocin. Specimens were assayed using microcomputed tomography and histomorphometry at 4 and 8 weeks postimplantation. Results: The histologic results showed an increase in new bone formation in the experimental groups compared with the control group. Both bone volume/total volume and trabecular thickness of newly formed bone within CSDs were the highest, and trabecular spacing was the lowest, in the 3 × 10 6 group at 8 weeks for the most favorable outcome. The results showed that the amount of new bone was greatest in the 3 × 10 6 group by 8 weeks. Conclusions: ASCs enhanced vertical bone regeneration in calvarial defects in rats with type 2 DM, when used in association with bovine bone scaffolds. The findings suggest that a combination of ASCs and bovine bone scaffolds could improve bone quantity in vertical bone defects.